TAHAPAN PENGOLAHAN SIRTU UNIT CRUSHING PLANT PT. PUSAKA DEWA KRESNA KABUPATEN NABIRE PROVINSI PAPUA - Agus Hilapok; Hendri P. Perangin-Angin (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
To increase the production of the gravels processing, it is necessary to have a fairly mature plan with economical consideration. One of the conditions so that the business runs as planned, it takes a synergistic processing unit to achieve the desired goal. The study aimed to determine the production in the processing unit of PT. Pusaka Dewa Krisna. The method used in this research is a descriptive method, where the descriptive research method looks at the symptoms of one or more variables that are observed directly in the field. This method aims to collect all the information that will be used. The results of the research are for the size of the hopper area of 4.5m2 with a production capacity of 10.32 tons/m2 of crusher, Primary crusher capacity of 55.80 tons/hour, secondary crusher capacity of 22,322 tons/hour, cone crusher capacity of 50 tons/hour.